Control and non-progression of HIV-1 infection in sub-Saharan Africa: A case and review - P Patel; M Brooks; G Anabwani; M A Tolle (AOSIS, 2012)
Elite and viraemic controllers represent unique subsets of HIV-infected patients who may also be long-term non-progressors (LTNPs). LNTPs constitute an estimated 1 - 15% of the total HIV-positive population in the USA and Europe, but less is known about their epidemiology in sub-Saharan Africa. Though the exact mechanisms for long-term non-progression appear to be numerous and are still under investigation, research on elite controllers may hold the key to new therapeutics and vaccine development. The clinical management of such patients can be challenging, as there are no standard guidelines for treatment, particularly in resource-limited settings. We describe the case of an HIV-infected Botswanan man who is likely an elite or viraemic controller.